Cloning and expression of enterovirus 71 capsid protein 1 in a probiotic Bifidobacterium pseudocatenulatum. (1st January 2019) - Thinbanmai, T.; Lulitanond, V.; Mayo, B.; Lulitanond, A.; Panya, M.
Abstract: This study investigated cloning and expression of enterovirus 71 viral capsid protein 1 (EV71‐VP1) in Bifidobacterium pseudocatenulatum ( B . pseudocatenulatum ) M115. To achieve this, a codon‐optimized gene coding for EV71‐VP1 was analysed, designed, synthesized and cloned into a plasmid vector flanked by a transcriptional promoter and terminator sequences. The promoter was based on that of P919, a constitutive promoter of the gene encoding the large ribosomal protein of B . bifidum BGN4, while the terminator was based on that of the peptidase N gene of Lactococcus lactis . The construct was amplified in Escherichia coli XL1‐blue and then transferred into B. pseudocatenulatum M115 by electrotransformation. Western blot analysis revealed that the EV71‐VP1 was intracellularly expressed in B. pseudocatenulatum M115 under the control of the selected heterologous promoter. In addition, plasmid stability analysis showed the construct was maintained stably for more than 160 generations, enough for most future applications. The results derived from this study open the possibility to utilize the bacterium carrying a specific expression plasmid as cell factory for the production of proteins with high commercial and health‐promoting value. Significance and Impact of the Study: This study demonstrated the first successful expression of a codon‐optimized gene coding for enterovirus 71 viral capsid protein 1 (EV71‐VP1) in Bifidobacterium pseudocatenulatum M115, a novel probiotic strain isolated from human intestines. The EV71‐VP1 was constitutively expressed under the control of P919 promoter derived from B . bifidum BGN4 in the cytoplasm of bacterial cells supporting the use of heterologous promoter and terminator sequences for viral gene expression in Bifidobacterium species.